Implementation of cross-sectoral roles in promoting adolescent mental health: a case study - Lina Eta Safitri; Ovi Sofiya; Fitri Setyaningsih (Jurnal Cakrawala Promkes, 2026)
Mental health promotion requires collaboration across schools, families, health services, and communities to support adolescent psychosocial development. This study explored cross-sectoral roles in promoting adolescent mental health among teenagers in Sumbawa Regency. A descriptive qualitative design was employed, involving four informants. Data were collected through in-depth interviews and analyzed using content analysis, with triangulation to ensure validity. The study focused on early detection, mental health promotion activities, and peer-based cadre development. Findings indicate that collaboration among the school, the Community Health Center, and National Population and Family Planning Agency (BKKBN) supports promotive and preventive efforts. Early detection is conducted through periodic screening by the Community Health Center remains limited in coverage an dnot yet integrated into a continuous school-based system. Mental health promotion involves multiple stakeholders, including community leaders, but is largely event-based with limited monitoring and evaluation. Peer cadre development through the PIK-R program facilitates peer support and early identification, although its implementation remains informal and restricted to certain student groups. In conclusion, cross-sector collaboration strengthens school-based mental health promotion through integrated screening, outreach, and peer-based approaches. However, its sustainability depends on consistent coordination and institutional support.